Aberrant gray matter volume and cortical surface in paranoid-type delusional disorder - Wolf, Robert Christian; Hildebrandt, Viviane; Schmitgen, Mike; Pycha, Roger; Kirchler, Erwin; Macina, Christian; Karner, Martin; Hirjak, Dusan; Kubera, Katharina Maria; Romanov, Dmitry; Freudenmann, Roland Wolfgang; Huber, Markus (Neuropsychobiology, 2020)
Introduction:Delusions are core symptoms of schizophrenia-spectrum and related disorders. Despite their clinical relevance, the neural correlates underlying such phenomena are unclear. Recent research suggests that specific delusional content may be associated with distinct neural substrates.Objective:Here, we used structural magnetic resonance imaging to investigate multiple parameters of brain morphology in patients presenting with paranoid type delusional disorder (pt-DD,n= 14) compared to those of healthy controls (HC,n= 25).Methods:Voxel- and surface-based morphometry for structural data was used to investigate gray matter volume (GMV), cortical thickness (CT) and gyrification.Results:Compared to HC, patients with pt-DD showed reduced GMV in bilateral amygdala and right inferior frontal gyrus. Higher GMV in patients was found in bilateral orbitofrontal and in left superior frontal cortices. Patients also had lower CT in frontal and temporal regions. Abnormal gyrification in patients was evident in frontal and temporal areas, as well as in bilateral insula.Conclusions:The data suggest the presence of aberrant GMV in a right prefrontal region associated with belief evaluation, as well as distinct structural abnormalities in areas that essentially subserve processing of fear, anxiety and threat in patients with pt-DD. It is possible that cortical features of distinct evolutionary and genetic origin, i.e. CT and gyrification, contribute differently to the pathogenesis of pt-DD.
Gesehen am 17.08.2020